Model Pendekatan al-Maw’iẓah al-Ḥasanah Melalui Facebook : Model of al-Maw’iẓah al-Ḥasanah Approach Through Facebook - Ahmad Zohri, Nor’Aini (Journal of Al-Falah, 2025)
Facebook is the highest social media in the order of the most used social media by Malaysians. The preachers also use Facebook as one of the platforms to preach through social media. The most appropriate approach to use in Facebook is the al-Maw'iẓah al-Ḥasanah approach because it is aimed at the public. Therefore, this study aims to study the approach of al-Maw'iẓah al-Ḥasanah through Facebook by integrating a deep understanding of the wasilah dakwah Facebook and manhaj dakwah al-Maw'iẓah al-Ḥasanah based on the al-Maw'iẓah al-Ḥasanah Approach Model Through Facebook. This study is a qualitative study on Facebook of Ustazah Asma' Harun (UAH) as the subject of the study using the literature method to comprehensively study the approach of al-Maw'iẓah al-Ḥasanah through Facebook followed by the interview method conducted with the team members who operate his Facebook to study the strategy and implementation of da'wah using Facebook. The results of the study produced the al-Maw'iẓah al-Ḥasanah Approach Model Through Facebook which consists of preachers on Facebook namely techno-da'i, influencers, microcelebrities and celebrity preachers. Next, the delivery of da'wah by the preacher is delivered through the Facebook da'wah wasilah which the process consists of producing, delivering and disseminating da'wah content. The content production aspect consists of the Da'wah Presentation Feature followed by the content delivery aspect which consists of the approach of al-Maw'iẓah al-Ḥasanah and Islam as mawḍū' dakwah and finally the content dissemination is by fulfilling the way Facebook's algorithm works. The final element in this model is the target of da'wah as the recipient of the approach of al-Maw'iẓah al-Ḥasanah which shows some response to this approach which is to accept and respond to the advice given, instil love in dā'ī and mad'ū and limit oneself from continuing to do unrighteous things.